2023
DOI: 10.36660/abc.20220370
|View full text |Cite
|
Sign up to set email alerts
|

Valor Diagnóstico de Parâmetros Tridimensionais de Strain de Imagem de Speckle Tracking para Detecção de Disfunção Cardíaca Relacionada à Quimioterapia do Câncer: Uma Metanálise

Abstract: Resumo Fundamento Agentes quimioterápicos (por exemplo, antraciclinas, trastuzumabe) comumente usados para o tratamento de tumores malignos demonstraram ter efeitos cardiotóxicos, que estão associados a um prognóstico ruim. A ecocardiografia tridimensional tem sido usada para prever a disfunção cardíaca induzida pela quimioterapia do câncer. Objetivos Avaliação do desempenho diagnóstico de parâmetros de strain, área global de strain (AGS), strain longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(157 reference statements)
0
2
0
Order By: Relevance
“…In this issue of the Arquivos Brasileiros de Cardiologia (ABC Cardiol), Y Guan et al 10 reported the combined data of 9 prospective cohort studies, including 650 cancer patients (71% female) from China, Portugal, Romania, and Greece that assessed the value of 3D-STE to detect myocardial dysfunction related to oncological treatment. 10 The performance of 3D-global longitudinal, circumferential, and radial strains (GLS, GCS, GRS, respectively) and 3D-global area strain (GAS) against a gold standard definition of cardiotoxicity based on an LVEF decrease (thresholds varying from 5 to 10%) was summarized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Arquivos Brasileiros de Cardiologia (ABC Cardiol), Y Guan et al 10 reported the combined data of 9 prospective cohort studies, including 650 cancer patients (71% female) from China, Portugal, Romania, and Greece that assessed the value of 3D-STE to detect myocardial dysfunction related to oncological treatment. 10 The performance of 3D-global longitudinal, circumferential, and radial strains (GLS, GCS, GRS, respectively) and 3D-global area strain (GAS) against a gold standard definition of cardiotoxicity based on an LVEF decrease (thresholds varying from 5 to 10%) was summarized.…”
mentioning
confidence: 99%
“…In this issue of the Arquivos Brasileiros de Cardiologia (ABC Cardiol), Y Guan et al 10 reported the combined data of 9 prospective cohort studies, including 650 cancer patients (71% female) from China, Portugal, Romania, and Greece that assessed the value of 3D-STE to detect myocardial dysfunction related to oncological treatment. 10 The performance of 3D-global longitudinal, circumferential, and radial strains (GLS, GCS, GRS, respectively) and 3D-global area strain (GAS) against a gold standard definition of cardiotoxicity based on an LVEF decrease (thresholds varying from 5 to 10%) was summarized. Evidence on GLS is, undoubtedly, more abundant than for the other parameters, with 8 (out of 9) studies providing consensual data on its good performance; GLS sensitivity and specificity values that were pointed out in this meta-analysis were achieved, making it a potential candidate for immediate clinical use.…”
mentioning
confidence: 99%